The experience of international nursing students studying for a PhD in the U.K: A qualitative study - Stevenson Keith; Evans Catrin (BMC, 2011)
Abstract Background Educating nurses to doctoral level is an important means of developing nursing capacity globally. There is an international shortage of doctoral nursing programmes, hence many nurses seek their doctorates overseas. The UK is a key provider of doctoral education for international nursing students, however, very little is known about international doctoral nursing students' learning experiences during their doctoral study. This paper reports on a national study that sought to investigate the learning expectations and experiences of overseas doctoral nursing students in the UK. Methods Semi-structured qualitative interviews were conducted in 2008/09 with 17 international doctoral nursing students representing 9 different countries from 6 different UK universities. Data were analysed thematically. All 17 interviewees were enrolled on 'traditional' 3 year PhD programmes and the majority (15/17) planned to work in higher education institutions back in their home country upon graduation. Results Studying for a UK PhD involved a number of significant transitions, including adjusting to a new country/culture, to new pedagogical approaches and, in some cases, to learning in a second language. Many students had expected a more structured programme of study, with a stronger emphasis on professional nursing issues as well as research - akin to the professional doctorate. Students did not always feel well integrated into their department's wider research environment, and wanted more opportunities to network with their UK peers. A good supervision relationship was perceived as the most critical element of support in a doctoral programme, but good relationships were sometimes difficult to attain due to differences in student/supervisor expectations and in approaches to supervision. The PhD was perceived as a difficult and stressful journey, but those nearing the end reflected positively on it as a life changing experience in which they had developed key professional and personal skills. Conclusions Doctoral programmes need to ensure that structures are in place to support international students at different stages of their doctoral journey, and to support greater local-international student networking. Further research is needed to investigate good supervision practice and the suitability of the PhD vis a vis other doctoral models (e.g. the professional doctorate) for international nursing students.